2021
DOI: 10.1007/s00068-021-01640-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of displaced femoral neck fractures in patients with dementia: a comparison in mortality between hemiarthroplasty and pins/screws

Abstract: Introduction Dementia is common in patients with hip fractures and is strongly associated with increased postoperative mortality. The choice of surgical intervention for displaced femoral neck fractures (dFNF) in patients with dementia has been a matter of debate. This study aims to investigate how short- and long-term mortality differs between those who have been operated with hemiarthroplasty or pins/screws. Methods All patients with dementia and dFNF, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Other factors that have been demonstrated to affect adverse outcomes after surgery is the surgical method used, where internal fixation has been associated with lower risks compared with arthroplasty when the surgery is performed out-of-hours, while patients with dementia and dislocated cervical hip fractures had better outcomes when they underwent hemiarthroplasty rather than internal fixation. 22 25 However, no difference was seen in the outcomes measured in the current study when analyzing patients who underwent internal fixation, arthroplasty, had an extended surgical duration, or underwent surgery out-of-hours. One potential explanation for our findings could be the relatively short procedure time for hip fracture surgery; as most surgical techniques are relatively simple procedures the overall surgical trauma might result in less physiological strain compared to more complex surgeries with longer surgical durations.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Other factors that have been demonstrated to affect adverse outcomes after surgery is the surgical method used, where internal fixation has been associated with lower risks compared with arthroplasty when the surgery is performed out-of-hours, while patients with dementia and dislocated cervical hip fractures had better outcomes when they underwent hemiarthroplasty rather than internal fixation. 22 25 However, no difference was seen in the outcomes measured in the current study when analyzing patients who underwent internal fixation, arthroplasty, had an extended surgical duration, or underwent surgery out-of-hours. One potential explanation for our findings could be the relatively short procedure time for hip fracture surgery; as most surgical techniques are relatively simple procedures the overall surgical trauma might result in less physiological strain compared to more complex surgeries with longer surgical durations.…”
Section: Discussionmentioning
confidence: 58%
“…These comorbidities, along with the acute injury, have a negative impact on the cardiovascular system as well as other organ systems, which may affect the postoperative risk of adverse events 7–9 14. Furthermore, studies have shown that several other factors could increase the risk of postoperative adverse events after hip fracture surgery, such as surgical duration, out-of-hours surgery, and dementia 5 19–22 24 25 31. However, these variables have not been taken into account in the previous studies on this topic 12 13…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations